Project-Based Learning (PjBL) Mini Drama to Enhance Motivation and Japanese Communication Skills of Tourism Students - Farisya, Ghaida; Via Luviana Dewanty; Hafizahra Firyalhasya Aida Rahadiyan (Chi e Journal of Japanese Learning and Teaching, 2024)
This study discusses how the project-based learning (PBL) method in the form of mini-drama, can improve oral Japanese communication skills and understanding of Japanese culture in the tourism study program at Garut University. The theme of the mini drama chosen was the differences in the habits of Japanese and Indonesian tourists in the context of hospitality. The mini drama was performed in an annual event organized by the tourism study program. The mini drama is 25 minutes long with three different story segments and conflicts. This study used a qualitative approach to measure the improvement of Japanese speaking ability as well as students' perceptions of the application of learning methods. The results showed that the PBL method applied can improve the Japanese oral communication skills of tourism study program students, especially communication using respectful language varieties (keigo) and formal language varieties (teineigo). Students also gave positive responses to the application of the PBL method because it was considered to increase learning motivation, self-confidence, better understanding of the socio-culture of Japanese society, and the ability to collaborate with students from various levels. This study provides implications for curriculum development and Japanese language learning methods in tourism study programs, as well as contributing to research on the effectiveness of the PBL method in Japanese language learning.